Association Of An Interleaved Boost-flyback Converter And A Full Bridge Converter In A Soft-switching High Power Factor Power Supply - Carlos A. Gallo; Fernando L. Tofoli; João A. Corrêa Pinto; Ernane A. A. Coelho; Luiz C. Freitas; Valdeir J. Freitas; João Batista Vieira Jr. (Eletrônica de Potência, 2004)
This work presents the analysis of a high power factor power supply operating at high switching frequency. An almost unity input power factor is obtained when an interleaved Boost-Flyback converter associated with a nondissipative snubber is used as a preregulator stage. A Full-Bridge converter is used as DC-DC stage, as the combination of both topologies results in the proposed SMPS. Theoretical background on each one of the converters is presented, and analytical results on the proposal are discussed in order to validate the proposal.